CUE-COMPETITION IN FEAR POTENTIATED STARTLE CONDITIONING IN HUMANS - Pinto, Jorge A.; Pineida, Alfredo (Mexican Journal of Behavior Analysis, 2020)
In two experiments of fear-potentiated startle, human participants were trained in a discrimination task, in which a stimulus A was paired with a wrist shock, while another stimulus, B, was not (A+B-). In a test, participants were assessed for startle by presenting an air-puff either alone or in the presence of the trained stimulus. In Experiment 1, evidence of discriminative learning was found in the form of a reliably greater startle to the air-puff in the presence of A than in the presence of B, and in the absence of any cue. In Experiment 2, after A+B- training (counterbalanced visual and vibrotactile cues), cues A and B were compounded with novel auditory cues X and Y and reinforced (AX+BY+), which is the standard design for cue-competition. In test, there was evidence of cue competition only in those participants in which A and B were the visual and vibrotactile cues, respectively. In this subgroup, responding in the presence of the redundant cue X was reliably lower than in the presence of Y, and not different from responding to the air-puff alone, indicating that X was blocked by A. We speculate that the absence of such an effect in the subgroup in which A was vibrotactile and B was visual might be due to some unexpected generalization between vibrotactile and auditory cues.